Rancang Bangun Sistem Kontrol dan Monitoring Alat UkurBesaran Listrik Berbasis IoT (Internet of Things) - Yani Ridal (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
All work and human needs at this time are very dependent on the presence of electrical energy, especially on household needs. Human negligence in the use of electrical energy will lead to waste which also has an impact on increasing the cost of using electrical energy. Therefore, a tool is needed that is capable of monitoring, controlling the use of electrical energy and is able to limit the current usage of the load, even though the user of electrical energy is not at home. Of course, to make this tool you need a voltage sensor, current sensor, relay, Arduino UNO Wifi, and a power supply. The voltage sensor used is ZMPT101B which functions to read the voltage value, the current sensor used is ACS712 which functions to read the current value, the relay functions to limit the current value in a way when the current sensor reads the current value at the load and then the author sets it in the program by limiting the current may enter by 10 A and if it exceeds the current limit this monitoring device will turn off, the Arduino UNO Wifi functions to process data read from the voltage and current sensors, and the WIFI module functions to send data to the Blynk Cloud server so that it can be viewed with an internet network. From the results of the control test by turning on and off the tool with a radius of 12 km. The test results were measured for 2 hours on the load of incandescent lamps, televisions, fans, laptop chargers, dispensers, irons and Rice Cookers using ZMPT101B and ACS712 resulting in a voltage measurement error of 0.93% and a current measurement error of 1.14%